The impact of green human resource management and green supply chain management practices on sustainable performance - Abdulrahim Zaid, Ahmed Adnan (2019)
A growing amount of studies have focused on green supply chain management (GSCM) and green human resource management (GHRM) practices that incorporate ecological thinking, these practices are expected to affect Triple Bottom Lines (TBL) of sustainability of manufacturing organisations. This study aims at investigating the linkage between GHRM practices, internal and external GSCM practices, as well as their impact on the TBL of sustainability performance among Palestinian manufacturing organisations. To meet these objectives, 17 hypotheses tailored by the theoretical lenses of Resource Based View (RBV) was proposed to test the theorized relationship of GHRM practices, GSCM practices and TBL of sustainability. A quantitative method is applied in which data is collected from a customised survey with 121 firms functioning in the most pollutant manufacturing sectors such as food, chemical, and pharmaceutical sectors in Palestine. The data analysis was conducted using SmartPLS 3.2.7. The results show that both GHRM and GSCM practices have a positive effect on sustainable performance in a joint manner. Moreover, the results also revealed that GHRM practices have a direct significant effect on sustainable performance as well as a significant mediating effect with GSCM practices. In particular, internal GSCM practices positively mediate between GHRM practices and sustainable performance, whereas external GSCM practices mediate only the relationship between GHRM practices and environmental dimension of sustainable performance, thus suggesting absence of awareness among manufacturers regarding the effectiveness of this type of GSCM practices for an improved economic and social dimensions of sustainable performance, and calling for more attention from green training programs. This study provides some implications in terms of theory advancements and practical applications that can help practitioners to better understand the issues related to the GHRM practices, GSCM practices and sustainable performance of the manufacturing organisations.